Putting mission-oriented innovation policies to work: A case study of the German high-tech strategy 2025 - Florian Roth; Florian Wittmann; Miriam Hufnagl; Ralf Lindner (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2022)
Over the last years, numerous national governments as well as the European Union have initiated so-called missions to guide transformation processes and tackle grand challenges, such as climate change, digitalization and an aging society. Previous research on mission-oriented innovation pol-icies (MOIP) has mainly focused on conceptual reflections about mission goals and early stages of the implementation process, but paid little attention to the actual implementation of missions. The aim of the paper is to untangle and reveal the complex processes involved in developing and ap-plying MOIP concepts in political practice (e.g. the role of policy instruments and actors) and pro-vide insights for the advancement of mission approaches. To do so, we focus on the three stages of mission formulation, mission design and mission implementation. The three-fold framework al-lows delineating different areas of negotiation and contestation, exploring potential bottlenecks when bringing missions into action. The empirical part of the paper draws on the case of the German High-Tech Strategy 2025 (HTS) which entails twelve missions across different sectors. Even though the German Government offi-cially claims that the current HTS is guided by a mission-driven approach and 12 missions are de-tailed, the analysis finds considerable problems when it comes to translating this into practice in Germany's political landscape. Our findings call for a conceptual systemic underpinning of MOIP, which contributes to a reduction of complexity and provide better access to understanding the interplay of different instruments and their mix. This way, the discussion paper aims to contribute to a better understanding of the preconditions as well as the main challenges in putting missions to work and to inform the next generation of innovation policies that are currently being issued in Germany and elsewhere.
Keywords: 330; Technologiepolitik; Hochtechnologie; Wirtschaftspolitisches Ziel; Einführung; Deutschland